Prevalence and associated factors of pregnancy induced hypertension among pregnant women in public hospitals of Hadiya Zone, Central Ethiopia: A cross-sectional study - Zerfework Debebe Argago; Nebiyu Dereje; Neena Elezebeth Philip (PLoS ONE, 2025)
Background Pregnancy-induced hypertension is one of the global public health burdens contributing to several adverse perinatal outcomes. However, data on the prevalence and associated factors of PIH is limited in Hadiya Zone, central Ethiopia. Methods We conducted a cross-sectional study among women attending antenatal care in the four public hospitals in the Hadiya zone from August 1, 2023, to January 30, 2024. The total sample size (433) was proportionally allocated to each hospital. Data were collected by face-to-face interview using a structured questionnaire. Blood pressure was measured by a digital Sphygmomanometer, and Pregnancy-induced hypertension status was considered if systolic blood pressure was ≥ 140 mmHg and/or diastolic blood pressure ≥90 mmHg on two measurements among pregnant women with gestational age > 20 weeks. Factors associated with Pregnancy-induced hypertension were identified by multivariable binary logistic regression analysis, as expressed by adjusted odds ratio (aOR) and its 95% confidence interval. Results The mean age of the participants was 29.4 years (SD = ±4.6), and the majority of women were multiparous (59.6%). The prevalence of Pregnancy-induced hypertension was 13.4% (95% CI: 10.2% – 16.9%), of which 81% were preeclampsia. In the multivariable analysis, PIH was associated with, the poorest wealth index (aOR = 0.26, 95%CI: 0.08–0.90), having a family history of hypertension (aOR = 12.52,95%CI: 4.52–34.62), overweight maternal BMI (aOR = 4.24, 95%CI: 2.06–8.72), and gestational age (aOR = 0.21 at 95% CI: 0.06–0.82). Conclusions More than 13 out of 100 pregnant women were found to have pregnancy-induced hypertension in the Hadiya zone, Southern Ethiopia. The high prevalence of Pregnancy-induced hypertension and its association with wealth index, gestational age, overweight/obesity and family history of hypertension/Pregnancy-induced hypertension underscores the need for targeted, tailored, and contextualized interventions to address Pregnancy-induced hypertension in the Hadiya zone. Creating awareness on Pregnancy-induced hypertension among pregnant women and the general population and enhancing early screening and detection services in the community and healthcare facilities need to be strengthened in the Hadiya zone.